EFEKTIVITAS KINERJA APARATUR DESA TERHADAP PERENCANAAN DANA DESA DI DESA SALO DUA KECAMATAN MAIWA KABUPATEN ENREKANG - Andiny, Arum Tri; Monalisa Ibrahim; Muhammad Ikbal (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
ABSTRACT Arum Tri Andiny, 2025. The Effectiveness of Village Apparatus Performance on Village Fund Planning in Salo Dua Village, Maiwa District, Enrekang Regency, (guided by Mrs. Monalisa Ibrahim and Mr. Muhammad Ikbal). This have a look at ambitions to decide the effectiveness of the overall performance of village equipment on village fund planning in Salo Dua Village and identify the factors that affect the planning. The research population amounted to 50 network leaders, with a saturated sampling technique, in which the whole population become sampled. This look at makes use of a descriptive quantitative technique with statistics series strategies through remark, questionnaires, and literature studies. facts evaluation became accomplished by using validity, reliability, and descriptive information checks the usage of IBM SPSS facts model 21.0. The results of the look at showed that the average overall performance variable of village apparatus turned into 61%, which became categorized as "good". The planning variable has a median of 68%, also within the "suitable" category. For factors that have an effect on village fund making plans, a mean of 63% become acquired, with a similar class. The responsibility thing changed into the maximum influential with the highest percentage of 67%. based totally on the ANOVA test, a Fcal cost of 30.804 and a importance of zero.003 have been acquired, which shows a full-size have an impact on among unbiased variables and village fund making plans. The partial check showed that the tcount of 5,740 changed into extra than the ttable of 1,677, so it may be concluded that the effectiveness of the performance of the village equipment has a substantial effect on the planning of village budget in Salo Dua Village, Maiwa District, Enrekang Regency. Keywords: Apparatus Performance and Planning